Centros Urbanos de la Civilización Caral: 21 años recuperando la historia sobre el Sistema Social - Guzmán García, Carlos Enrique (2019)
The title of this publication is overwhelming, names the settlements that developed around the year 3,000 a. C. in the valley of Supe fruit of a civilization with its own name: Caral. Nine urban centers in the Supe Valley are considered in this publication by Ruth Shady and her professional team. The discoveries made during the last 15 years in the valley of Supe (and Vichama, on the coast of Huaura) by the archaeologist Ruth Shady and her work team have been so huge that they have allowed her to state the existence of a social system (last title phrase).